The square-kagome quantum Heisenberg antiferromagnet at high magnetic fields: the localized-magnon paradigm and beyond - Derzhko, Oleg; Richter, Johannes; Krupnitska, Olesia; Krokhmalskii, Taras (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
We consider the spin-1/2 antiferromagnetic Heisenberg model on the two-dimensional square-kagome lattice with almost dispersionless lowest magnon band. For a general exchange coupling geometry we elaborate low-energy effective Hamiltonians which emerge at high magnetic fields. The effective model to describe the low-energy degrees of freedom of the initial frustrated quantum spin model is the (unfrustrated) square-lattice spin-1/2 XXZ model in a z-aligned magnetic field. For the effective model we perform quantum Monte Carlo simulations to discuss the low-temperature properties of the square-kagome quantum Heisenberg antiferromagnet at high magnetic fields. We pay special attention to a magnetic-field driven Berezinskii–Kosterlitz–Thouless phase transition which occurs at low temperatures.